Simultaneous versus Sequential Accelerated Corneal Collagen Cross-Linking and Wave Front Guided PRK for Treatment of Keratoconus: Objective and Subjective Evaluation - Waleed Ali Abou Samra; Dalia Sabry El Emam; Rania Kamel Farag; Hossam Youssef Abouelkheir (Journal of Ophthalmology)
Aim. To compare objective and subjective outcome after simultaneous wave front guided (WFG) PRK and accelerated corneal cross-linking (CXL) in patients with progressive keratoconus versus sequential WFG PRK 6 months after CXL. Methods. 62 eyes with progressive keratoconus were divided into two groups; the first including 30 eyes underwent simultaneous WFG PRK with accelerated CXL. The second including 32 eyes underwent subsequent WFG PRK performed 6 months later after accelerated CXL. Visual, refractive, topographic, and aberrometric data were determined preoperatively and during 1-year follow-up period and the results compared in between the 2 studied groups. Results. All evaluated visual, refractive, and aberrometric parameters demonstrated highly significant improvement in both studied groups (all P<0.001). A significant improvement was observed in keratometric and Q values. The improvement in all parameters was stable till the end of follow-up. Likewise, no significant difference was determined in between the 2 groups in any of recorded parameters. Subjective data revealed similarly significant improvement in both groups. Conclusions. WFG PRK and accelerated CXL is an effective and safe option to improve the vision in mild to moderate keratoconus. In one-year follow-up, there is no statistically significant difference between the simultaneous and sequential procedure.